Occupational Dermatosis (Nepalese Medical Journal, 2018)
Introduction: Occupational dermatosis is defined as any pathological condition of the skin for which job exposure can be shown to be a major direct or contributory factor. The commonest occupational dermatosis is a work-related contact dermatitis. The aim of the study was to find the pattern and diagnosis of occupational dermatosis in our community as no such study has been carried out in Nepal.Materials and Methods: This was a prospective study of 70 ambulatory patients with work-related dermatoses presented to the Dermatology Department of Kist medical. Data on socio-demographic characteristics, on lifestyle and temporal factor, the type of contact dermatitis, location and etiological factors were gathered through a structured questionnaire.Results: More females (n=39; 60%) cases were affected by contact dermatitis compared to men (n=31; 40%), without a significant difference (p=0.5). Most of our patients belonged to the age group of 20-39 years accounting to 38 cases (54%). The mean age of patients was 34 years old (16 – 70 year), with 49 (70%) of them living in urban area and 21 (30%) living in rural area, (p